DAMPAK KEHADIRAN BHAYANGKARA PEMBINA KEAMANAN DAN KETERTIBAN MASYARAKAT(BHABINKAMTIBMAS) DALAM PENANGANAN TINDAK PIDANA RINGAN (TIPIRING) DIWILAYAH HUKUM POLSEK MATUR KABUPATEN AGAM - amri, khairul (STIH Painan, 2023)
Security disturbances are events that cause disruption of security stability in the community, both criminal and social problems, which are now familiar to some Indonesian people, so it is deemed necessary to adopt the concept of Community Policing (Community Policing) or commonly abbreviated as